Decoding interchange: reducing daily urban stress through environmental engineering - De Wet, Julie (My University, 2011)
Stress is something that we can all relate to, have all experienced and is compounded by certain environments that people experience on a daily basis. This thesis will investigate how engineering one’s environment can be used to reduce the levels of stress one experiences. It will research the physiological factors that are able to be affected through architectural intervention, and the means through which this can be achieved. It will produce a set of evidence-based design recommendations and guidelines that could be applied to any physical environment. The conceptual design and implementation however, is site specific, as each place has individual problems. The proposed intervention focuses on the commuter passing through Johannesburg Park Station, and is a direct response to the largest stress factors within the station. The aim is to create an efficiency within the station by creating an ease of flow, legibility and clear movement routes. This will reduce the daily stress levels of the Park Station user